A Comparative Morphometrical Study of the Pecten Oculi in Different Avian Species - Mustafa Orhun Dayan; Tugba Ozaydın (The Scientific World Journal)
In this study was investigated the structure of pecten oculi in the ostrich, duck, pigeon, turkey, and starling. The pecten oculi of the ostrich was vaned type and made up primary, secondary, and few tertiary lamellae. However, duck, pigeon, turkey and starling had a pleated-type pecten oculi which displayed folded structure. The numbers of pleats of the pectens were 12, 13-14, 21-22, and 17 in duck, pigeon, turkey, and starling, respectively. Light microscopic investigation demonstrated that pecten oculi is basically composed of numerous capillaries, large blood vessels, and pigment cells in all investigating avian species. Capillaries were 20.23, 14.34, 11.78, 12.58, and 12.78 μm in diameter in ostrich, duck, pigeon, turkey, and starling, respectively. The capillaries are surrounded by thick basal membrane, and pigmented cells were observed around the capillaries.